Highly efficient dual-state emission and two-photon absorption of novel naphthalimide functionalized cyanostilbene derivatives with finely tuned terminal alkoxyl groups. (31st October 2022) - Ni, Yingyong; Yang, Longmei; Kong, Lin; Wang, Chengyuan; Zhang, Qichun; Yang, Jiaxiang
Abstract : Cyanostilbene and naphthalimide are incorporated to construct novel dual-state emission luminogens (DSEgens), which show highly efficient photoluminescence and two-photon absorption properties in both dilute solution and the aggregated state. Abstract : Organic luminogens (OLs) that are capable of yielding strong fluorescence in both solution and the aggregated state are referred to as dual-state emission luminogens (DSEgens). They are able to achieve multiple functions within onefold materials owing to their applicability in both states, and are highly desirable though less explored compared to conventional and aggregation-induced-emission (AIE) OLs. In this work, cyanostilbene (CS ) and naphthalimide (NI ) were incorporated to construct novel DSEgens, which were functionalized by various alkoxyl chains at the CS unit (NICS-X, X = M, E, P, and B, respectively) by balancing the design principles for conventional and AIE OLs. The photophysical properties of NICS-Xs were investigated by steady-state and transient spectroscopies, which showed strong emission with quantum yields of luminescence ( φ ) above 0.70 in both solution and solids. In particular, the attachment of different terminal alkoxyl chains finely tuned the emission wavelength of NICS-Xs with a difference of up to ∼59 nm. Single-crystal structure analysis and theoretical calculations of these materials suggested that simply changing the length of the terminal alkoxyl chains could effectively adjust the molecular conformation and packing structure, thus inducing large shifts of the photoluminescence (PL) spectra. In addition, NICS-Xs show two-photon absorption behaviors in the dual states with a cross section of up to 238 Goeppert-Mayer. On the one hand, our study reported a new family of DESgens and a straightforward strategy to finely tune their photophysical properties. On the other hand, the correlations between the photophysical properties and the molecular/solid-state structures were revealed, which suggested new design ideas for developing novel high-performance DSEgens.